Hidden Text: Imaging and reading an ancient tablet encased in an envelope. - Siddall, Luis R.; Raymond, Carla A.; Bevitt, Joseph J. (Buried History: The Journal of the Australian Institute of Archaeology, 2019)
A tablet from Nimrud, which is encased in an inscribed clay envelope IA5.074 (ND 3430), was imaged at the Australian Synchrotron Imaging Medical Beamline (IMBL). This confirmed that there was a cuneiform tablet inside the envelope, the text of which could be read. The paper provides the details of the imaging, describes the tomography, offers a reading of the enclosed tablet and comments on the variation between the text on the envelope and tablet and the significance of this for Assyrian contract law.